Pemanfaatan QGIS untuk Pembuatan Peta Agrowisata Desa Ibru dalam Program Inovasi Desa - Dwi Lestari, Fitri; Eka Hervy, Nazwa; Jaya, Asirman; Tri Maulana Ramadhan, Ikhsan; Arsa, Daniel (Green Publisher Indonesia, 2024)
Effective management of rural areas requires accurate maps to support strategic planning and sustainable development. Ibru Village in Muaro Jambi Regency, which has won the Innovative Village award, faces challenges in mapping strategic locations such as agro-tourism areas, biopharmaceutical land, and potential sleeping land. This research aims to compile a comprehensive map based on Geographic Information System (GIS) using QGIS open-source software. The methods used include field surveys, interviews with village officials and local communities, and secondary data analysis from satellite imagery. The results of the study identified five strategic agro-tourism locations in Ibru Village, including the Clean Water Source Area and the Turmeric Processed Production House, which have the potential to be developed as educational tourism destinations. In addition, the resulting map contains information on land types, including agricultural land, plantations, and settlements. This data provides in-depth insights into the geographical characteristics of villages, which are the cornerstone of resource management and data-driven planning. This research demonstrates how GIS technology can be integrated with a participatory approach to produce maps that are relevant to local needs. The results not only contribute to the development of science in the field of GIS but also empower the people of Ibru Village in supporting sustainable development. This study is expected to be a model that can be applied in other villages in Indonesia with similar challenges and potential.